Pengaruh Motivasi, Kepuasan, dan Lingkungan Kerja Terhadap Kinerja Karyawan Divisi Shipping Garment PT. Danliris Sukoharjo. - Endra Wahyu Rochmadi; Istiatin; Istiqomah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Employees of the Shipping Garment Division of Sukoharjo are the focus of this study. The purpose of this study is to determine the Influence of Motiv|ation, S|atisf|action, |and Work Environment on the Perform|ance of Employees of the Shipping Garment Division of PT. Danliris Sukoharjo. Descriptive quantitative methodology is used in this study. Employees of the Shipping G|arment Division |are the popul|ation of the study, |and 72 responses |are the s|ample. The results of d|at|a |an|alysis show th|at the t-test of work motiv|ation is signific|ant (0.000 <0.05) |and re|aches t-count> t-t|able (3.211> 1.994). Job s|atisf|action is signific|ant (0.000 <0.05) |and t-count> t-t|able (2.057> 1.994). work environment is signific|ant (1.178> 0.05) |and t-count <t-t|able (1.178 <1.994). Therefore, employee perform|ance |at PT D|anliris Sukoh|arjo is significantly influenced by motivation and product satisfaction, but is not influenced by the work environment.